2022
DOI: 10.1002/aenm.202103422
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Order in Y‐Series Non‐Fullerene Solar Cells to Realize High Open‐Circuit Voltages

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/aenm.202103422.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 93 publications
2
52
0
Order By: Relevance
“…The observed dependence of the device performance on the processing conditions and blend composition suggested a strong role of the molecular arrangements and order in the blend film. [24][25][26][27] This insight was further supported by the observation that side-chain modifications have a great impact on device performance. Side-chain modifications are well-known to alter the aggregation behavior and long-range order.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The observed dependence of the device performance on the processing conditions and blend composition suggested a strong role of the molecular arrangements and order in the blend film. [24][25][26][27] This insight was further supported by the observation that side-chain modifications have a great impact on device performance. Side-chain modifications are well-known to alter the aggregation behavior and long-range order.…”
Section: Introductionmentioning
confidence: 90%
“…Side-chain modifications are well-known to alter the aggregation behavior and long-range order. [23,[25][26][28][29][30][31][32][33][34][35][36][37][38][39][40] It is well-known that the performance of OSCs does not only depend on the material itself, but rather on the arrangement and orientation of individual molecules with respect to neighboring molecules. It is the local morphology and the resulting intermolecular interactions that control the energy levels as well as optical and electronic properties of the material, including the efficiency of exciton dissociation and charge extraction in a device.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interrelation between structural order, energetic disorder and device performance was highlighted in a recent study by Neher and co-workers. 97 Here, the authors performed temperature-dependent charge transport, charge recombination and V OC studies on blends of PM6 with either Y6 or N4. Compared to Y6, N4 exhibits slightly longer side chains, with the result of better solubility, less strong aggregation, and stronger intermixing with the PM6 donor phase.…”
Section: Energetic Disorder In Non-fullerene Acceptorsmentioning
confidence: 99%
“…36 This is because an electron–hole pair in the charge separated state has many more options to distribute in the blend volume than when it is bound in an exciton or in a charge transfer state. 75 However, our own recent studies showed a pronounced decrease of the free carrier density with temperature, 76 which questions a strong contribution by entropy-driven processes. An alternative approach is to consider the presence of sub-bandgap states not accessible by our spectroscopy.…”
Section: Resultsmentioning
confidence: 93%